English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please help me to solve my homework.

2007-01-05 21:28:12 · 8 answers · asked by mishi khan 1 in Science & Mathematics Mathematics

8 answers

This is a (false) proof that 1 = 2:

Let x = 1 and y = 1. Then,

x = y

If we square both sides,

x^2 = y^2

Therefore

x^2 - y^2 = 0

Back to x = y, if we multiply both sides of this equation by y, we obtain

xy = y^2

Therefore

xy - y^2 = 0

We have two equations that are equal to 0 now, so we can equate them to each other.

x^2 - y^2 = xy - y^2

Let's factor both sides.

(x - y)(x + y) = y(x - y)

Now, let's divide both sides of the equation by (x - y).

x + y = y

Plugging in the values x = 1 and y = 1 back in the equation

1 + 1 = 1, OR
2 = 1

*****
This is, of course, a false proof. The invalid step was when we divide both sides by (x - y), because (x - y) is equal to 0 (since
x = 1 and y = 1). All it takes is an invalid step in order to invalidate a claim.

Many people don't recognize this idea of an "invalid step" when presented with the proof that 0.9(repeating infinitely) = 1.

2007-01-05 21:38:50 · answer #1 · answered by Puggy 7 · 1 0

I think you can only "prove" that the assumption 1=2 is wrong by using a counterexample like an answer above mine.

2007-01-06 05:43:56 · answer #2 · answered by coachandybrown 2 · 0 0

I believe mmcall made an error in factoring the eqation.

a2 - b2 = ab-b2
(a+b)(a-b)=b(a-2)
assuming a=b ...
2a=0
a=0 b=0
...doesn't work

2007-01-06 05:44:42 · answer #3 · answered by C J 3 · 0 0

1=1
x^2=y^1
when the base no.s are we can compare the powers so,
2=1
proved.

2007-01-06 07:03:53 · answer #4 · answered by juno 2 · 0 0

Assume a = b then:
a2 = ab
a2 - b2 = ab-b2
(a-b)(a+b) = b(a-b)
a+b = b
b+b = b
2b = b
2 = 1

2007-01-06 05:31:01 · answer #5 · answered by mmcall 2 · 0 0

x=y=1

x=y
xx=yx or xsquare=x product y
subtract yy from both sides we get xx-yy=xy-yy
factorise and we get y(x-x)=(x+y)(x-y)
divide by(x-y){actyually, it means divide by zero} we get y=x+y
hence, 1=2
this is because you are actually dividing by 0 which gives this problem

2007-01-06 05:37:16 · answer #6 · answered by new_einstein 2 · 0 0

Question was not clear

2007-01-06 05:40:01 · answer #7 · answered by --> ( Charles ) <-- 4 · 0 0

are you completely insane????? that is a false equation!!!!!!

2007-01-06 05:31:01 · answer #8 · answered by Bryan Yanguas 1 · 0 0

fedest.com, questions and answers